Cardiac remodelling – Part 2: Clinical, imaging and laboratory findings. A review from the Study Group on Biomarkers of the Heart Failure Association of the European Society of Cardiology. (16th May 2022) - Aimo, Alberto; Vergaro, Giuseppe; González, Arantxa; Barison, Andrea; Lupón, Josep; Delgado, Victoria; Richards, A Mark; de Boer, Rudolf A.; Thum, Thomas; Arfsten, Henrike; Hülsmann, Martin; Falcao‐Pires, Inês; et al.
Abstract : In patients with heart failure, the beneficial effects of drug and device therapies counteract to some extent ongoing cardiac damage. According to the net balance between these two factors, cardiac geometry and function may improve (reverse remodelling, RR) and even completely normalize (remission), or vice versa progressively deteriorate (adverse remodelling, AR). RR or remission predict a better prognosis, while AR has been associated with worsening clinical status and outcomes. The remodelling process ultimately involves all cardiac chambers, but has been traditionally evaluated in terms of left ventricular volumes and ejection fraction. This is the second part of a review paper by the Study Group on Biomarkers of the Heart Failure Association of the European Society of Cardiology dedicated to ventricular remodelling. This document examines the proposed criteria to diagnose RR and AR, their prevalence and prognostic value, and the variables predicting remodelling in patients managed according to current guidelines. Much attention will be devoted to RR in patients with heart failure with reduced ejection fraction because most studies on cardiac remodelling focused on this setting. Abstract : Basic mechanism and main predictors of cardiac remodelling. The net balance between the effects of ongoing cardiac damage and heart failure (HF) therapies will drive cardiac geometry and function towards a further worsening (adverse remodelling) or an improvement (reverse remodelling). The main predictors of adverse versus reverse remodelling are listed; see text for further details. Increased left ventricular (LV) size has been associated with a greater likelihood of reverse remodelling, although very dilated left ventricles are unlikely to undergo reverse remodelling. Lower baseline values of soluble suppression of tumorigenesis‐2 (sST2) correspond to <48 ng/ml, which was reported to independently predict reverse remodelling. LGE, late gadolinium enhancement; LVEF, left ventricular ejection fraction; M, men; W, women.